The Role of Social Media in Strengthening Religious Moderation Amidst Digital Politics in Indonesia - Luthfiyah Ramadhani (GoResearch - Research & Publishing House, 2025)
Amidst the rapid development of digital politics, social media has become a discursive space that influences patterns of religious interaction in Indonesia. Platforms such as Instagram, TikTok, and Twitter are not only means of communication, but also battlegrounds for narratives between religious moderation and extremism. This study aims to conduct an in-depth analysis of how social media contributes to strengthening the values of religious moderation through a descriptive qualitative approach using a literature review method. The findings reveal that young people, digital religious figures, and online communities play a crucial role in spreading messages of peace through creative, educational, and contextual content. However, challenges such as low digital literacy, algorithmic echo chambers, and the politicization of religion in digital campaigns remain major obstacles. Therefore, synergy between the government, civil society, and digital platforms is needed to make social media a strategic tool in building an inclusive, tolerant, and sustainable space for religious diversity.